2017
DOI: 10.3389/fphys.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Orexin System: The Key for a Healthy Life

Abstract: The orexin-A/hypocretin-1 and orexin-B/hypocretin-2 are neuropeptides synthesized by a cluster of neurons in the lateral hypothalamus and perifornical area. Orexin neurons receive a variety of signals related to environmental, physiological and emotional stimuli, and project broadly to the entire CNS. Orexin neurons are “multi-tasking” neurons regulating a set of vital body functions, including sleep/wake states, feeding behavior, energy homeostasis, reward systems, cognition and mood. Furthermore, a dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 85 publications
(96 reference statements)
3
118
0
5
Order By: Relevance
“…Orexin is a neuropeptide secreted by the lateral hypothalamus (LH) with low levels in the CSF during sleep and high levels during wake (Chieffi et al, 2017). Darkness activates orexin neurons in nocturnal rodents (Marston et al, 2008), while orexin suppresses the SCN neurons either directly or indirectly through augmenting the IGL-mediated suppression of the SCN neurons (Belle et al, 2014; Palus et al, 2015).…”
Section: Hormones and Neuropeptides In Metabolic Functions Of The Cenmentioning
confidence: 99%
“…Orexin is a neuropeptide secreted by the lateral hypothalamus (LH) with low levels in the CSF during sleep and high levels during wake (Chieffi et al, 2017). Darkness activates orexin neurons in nocturnal rodents (Marston et al, 2008), while orexin suppresses the SCN neurons either directly or indirectly through augmenting the IGL-mediated suppression of the SCN neurons (Belle et al, 2014; Palus et al, 2015).…”
Section: Hormones and Neuropeptides In Metabolic Functions Of The Cenmentioning
confidence: 99%
“…Thus, orexin enhancement of CREB phosphorylation would enhance TWAA memory retention in O/A3 mice. Finally, it is possible that exogenous OXA might improve memory in O/A3 mice through induction of dentate gyrus neurogenesis, as several studies have demonstrated that orexin A induces neurogenesis in the dentate gyrus of rats and mice [13,46,57]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of several recent studies have led to propose the involvement of the orexinergic system in the pathophysiology of mood disorders. The orexinergic system orchestrates various aspects disturbed in mood disorders, such as sleep and arousal, behavioural and neuroendocrine responses to stress, reward‐seeking behaviours, energetic homeostasis, learning and memory, and in this is case this is achieved via direct projections to the medial prefrontal cortex (Chieffi et al., ; Li, Hu, & de Lecea, ; Li et al., ). Orexinergic neurons receive a variety of signals related to environmental, physiological and emotional stimuli, and project broadly to the entire central nervous system: the hypothalamic orexin system directly and strongly innervates and excites noradrenergic, dopaminergic, serotonergic, histaminergic and cholinergic neurons.…”
Section: Methodsmentioning
confidence: 99%